UJI EFEK ANTIINFLAMASI EKSTRAK ETANOL DAGING BUAH LABU KUNING (Cucurbita moschata D.) TERHADAP EDEMA PADA TELAPAK KAKI TIKUS PUTIH JANTAN GALUR WISTAR (Rattus novergicus) - Senewe, Merry; Yamlean, Paulina V.Y; Wiyono, Weny (PHARMACON, 2013)
ABSTRACT Inflamation is a protective response of body from injury of cell.Edema is an indication of inflammation.Pumpkin pericarp contains of flavonoid which has potency to decrease edema.The aims of this research were to study antiinflamation effect of ethanolic extract of pumpkin pericarp (Cucurbita moschata D.) with concentration 5, 10 and 20%on edema of white rat legs strain wistar.The subjects in this research were 15 white male rat strain wistar which divided into 5 groups, namely negative control (CMC),Â  positive control (Piroksikam) and extract group with concentration 5, 10 and 20%.Induction of 5% of chicken albumin on rats left leg lead to edema formation, followed with induction of CMC, Piroksikam solution and extractper oral. Measurement of edema volume was done using plestimometer, and observation of edema were made every 6 hours. The result shows that there were significant administration effects of pumpkin pericarp extract with concentration 5 and 10%. As a conclusion, ethanol extract of pumpkin pericarp exhibit potency to decrease edema.